Thiopurines vs methotrexate: Comparing tolerability and discontinuation rates in the treatment of inflammatory bowel disease. Issue 7 (14th August 2020) - Vasudevan, Abhinav; Parthasarathy, Nina; Con, Danny; Nicolaides, Steven; Apostolov, Ross; Chauhan, Ayushi; Bishara, Maria; Luber, Raphael P.; Joshi, Neetima; Wan, Anna; Rickard, James A.; Long, Tony; et al.
Summary: Background: There are safety concerns regarding immunomodulators (thiopurines and methotrexate) for treatment of inflammatory bowel disease (IBD). Aim: To compare the long‐term tolerability, and persistence of thiopurine and methotrexate therapy in IBD. Methods: A retrospective cohort study was performed at two hospitals between 1 January 2004 and 31 December 2016 for patients commenced on thiopurines or methotrexate for IBD. Treatment discontinuation rates, intolerances and disease activity were obtained from medical records. Results: There were 782 patients commenced on immunomodulator therapy; 244 (31%) on methotrexate with folate (67% subcutaneous therapy) and 538 (69%) on thiopurine (73% azathioprine). Median follow‐up was 42 vs 47 months ( P = 0.09). In patients on thiopurines, median 6‐TGN was 298 pmol/8 x 10 8 RBCs, while the median dose of methotrexate was 25 mg weekly. Methotrexate recipients had a higher rate of prior immunomodulator intolerance, were typically older and had a longer disease duration (54% vs 3%, median 43 vs 36 years, 6 vs 5 years, respectively, each P < 0.05). Overall, 208 (27%) discontinued therapy due to adverse events, (40% on methotrexate vs 19% on thiopurines, P < 0.001), including nausea (18% vs 4%), fatigue (7% vs 2%) and hepatotoxicity (8% vs 2%, each P < 0.001). Hospitalisations from adverse events (0.8% vs 0.9%) and serious infections (9% vs 12%), and deaths (1% vs 0%) were comparable between groups (all P > 0.05). Discontinuation due to adverse events occurred later in patients on methotrexate than on thiopurines (median 7 vs 5 months, P = 0.08). Conclusion: Discontinuation of methotrexate occurred at rates twice that of dose‐optimised thiopurine therapy.